2015
DOI: 10.1177/1758834015599389
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal growth factor receptor 2 positive (HER2+) metastatic breast cancer: how the latest results are improving therapeutic options

Abstract: Human epidermal growth factor receptor 2 positive (HER2+) metastatic breast cancer (MBC) remains an incurable disease, and approximately 25% of patients with HER2+ early breast cancer still relapse after adjuvant trastuzumab-based treatment. HER2 is a validated therapeutic target that remains relevant throughout the disease process. Recently, a number of novel HER2 targeted agents have become available, including lapatinib (a small molecule tyrosine kinase inhibitor of both HER2 and the epidermal growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 94 publications
0
33
0
1
Order By: Relevance
“…Several clinical trials showed the beneficiary effects of T-DM1 in the HER2-positive metastatic setting and in patients with prior exposure to trastuzumab and lapatinib. [40]…”
Section: Resultsmentioning
confidence: 99%
“…Several clinical trials showed the beneficiary effects of T-DM1 in the HER2-positive metastatic setting and in patients with prior exposure to trastuzumab and lapatinib. [40]…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of T‐DM1 to lapatinib and capecitabine in the second‐line treatment setting showed that T‐DM1 had less toxicity and a significant OS improvement (30.9 months vs 25.1 months, HR 0.68, 95%CI 0.55 to 0.85, P < .001) . In current practice, T‐DM1 is the preferred second‐line therapy for HER2‐positive metastatic breast cancer …”
Section: Clinically Relevant Drug‐target Biomarkersmentioning
confidence: 99%
“…29 In current practice, T-DM1 is the preferred second-line therapy for HER2-positive metastatic breast cancer. 30 Current clinical practice guidelines recommend HER2 testing on every primary invasive breast cancer and on metastatic sites (if stage IV and specimen becomes available), especially in patients who previously tested HER2 negative and present with disease recurrence. The decision to recommend HER2-targeted treatment should be delayed if HER2 status cannot be determined and additional testing to establish tumor HER2 status is necessary to guide therapeutic decisions.…”
Section: Her2 Overexpression/amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, trastuzumab, pertuzumab, lapatinib, and trastuzumab emtansine (T-DM1) are approved for use in different clinical settings in patients with HER2-positive breast cancer. All of the above inhibit the HER2 pathway, albeit using different strategies [12,13]. Trastuzumab is a recombinant humanized monoclonal antibody that binds the extracellular subdomain IV with internalization and degradation of the HER2 receptor.…”
Section: Introductionmentioning
confidence: 99%